AUTOMATIC LINEAMENT ANALYSIS OF AERIAL PHOTOGRAPH AND SATELLITE IMAGES IN WAYANG WINDU GEOTHERMAL FIELD AND ITS SURROUNDING, JAWA BARAT PROVINCE - ADWIN HAFIZSYAH (NIM : 12114042), RIFQY
Located in the ring of fireÃ‚Â’s zone made Indonesia has a huge geothermal energy potential. Geothermal energy is one of the renewable energy that more environmental friendly for use of electrical generator than fossil fuel. ThatÃ‚Â’s why we need to further our understanding of geothermal energy potential if we consider developing an advanced renewable energy electric generator system. Geological structures such as fault and fractures may become an indication of a permeable zone of geothermal fluids through cracks that appear inside the rocks. Those geological structures can be observed through lineaments that appear in satellite images and aerial photograph. Lineaments are extracted from Digital Elevation Models (DEM) from satellite images and aerial photograph with several pixels variation to determine the effect of pixel size on automatic lineaments extractionÃ‚Â’s results, and to see the relationship between lineaments of Wayang Windu Geothermal field and the others geothermal area around it. Automated lineaments extractionÃ‚Â’s results from DEMs with pixel sizes of 0,5 m, 1 m, 2 m, 3 m, 4 m, 5 m, 10 m, 15 m, and 20 m from aerial photograph, DEMNAS images, and SRTM images show that when we use the same parameters for them, larger pixel size will have longer lineaments and smaller in quantity than those with smaller pixel size. Also, the types of image (satellite images or aerial photographs) used for lineaments extraction doesnÃ‚Â’t affect the results. And from the lineament density map, the lineaments of smaller pixel size images will have more broad distribution area than those with larger pixel size. The surface geothermal manifestation such as hot springs show a good correlation with smaller pixel size (≤5m), those manifestations are located in moderate to high lineaments densityÃ‚Â’s zone. Based on the extracted lineaments of SRTM images, each of the geothermal fields (Wayang Windu, Darajat, Kamojang, and Patuha) have local geological structures that greatly affect the lineaments extraction result. All of the lineaments of geothermal fields shows NE-SW as the general direction, namely N24E for Kamojang field, N65E for Patuha field, N57E for Darajat field, and N51E for Wayang Windu field. And if we view them from a broader perspective by expanding the observation area with the Wayang Windu field as the center, the general direction of the lineaments doesnÃ‚Â’t show a major change. The general directions by expanding the observation area by 4,5 km, 9 km, 13,5 km, 18 km, 22,5 km, dan all of the SRTMÃ‚Â’s scene are N57E for 4,5 km, N52E for 9 km, N47E for 13,5 km, N46E for 18 km, N43E for 22,5 km, and N43E for all of the SRTMÃ‚Â’s scene.